Effect of Early Enteral Nutrition on Serum Inflammatory Factors and Intestinal Mucosal Permeability in Patients with Severe Acute Pancreatitis - Li, Pu; Jian, Jin-Ni; Chen, Rui-Lin (Turkish Journal of Gastroenterology, 2021)
Background: To analyze the effect of early enteral nutrition on serum inflammatory factors and intestinal mucosal permeability in patients with severe acute pancreatitis. Methods: A total of 55 patients with severe acute pancreatitis were divided into 2 groups: the control group (n = 27), who received routine treatment and the observation group (n = 28), who received early enteral nutrition. The expression of serum inflammatory factors and the permeability of the intestinal mucosa were compared between the 2 groups before and after treatment, and rates of infection and mortality within 30 days were statistically analyzed. Results: The recovery duration of serum and urine amylase and the length of hospital stay in the observation group were shorter than those in the control group. The white blood cell counts, levels of procalcitonin, and the expression of interleukin-6 (IL-6) in the observation group were lower than those in the control group 7 days after the treatment was commenced, and the differences were statistically significant (P < .05). The concentration of diamine oxidase in the serum and the urinary lactulose to mannitol (L/M) ratio in the observation group were lower than those in the control group 7 days after treatment was commenced. The infection rate in the observation group (21.43%) was lower than that in the control group (51.85%) (P < .05). There was no difference in the 30-day mortality between the 2 groups (P > .05). Conclusion: Early enteral nutrition may reduce the expression of serum inflammatory factors, decrease the permeability of the intestinal mucosa, and improve the prognosis of patients with severe acute pancreatitis.